Abordagens de gêneros discursivos em livros didáticos de língua inglesa aprovados pelo PNLD 2024 - Rafael Gonçalves Silva Freire (2024)
Textbooks are still the main source of content for the curricular components of Basic Education (Coracini, 1999). For this reason, the Programa Nacional do Livro e Material Didático (PNLD) invests resources in the evaluation and approval of textbooks used in public schools. Bearing that in mind, the present research carried out an analytical study of two collections of English language textbooks for the final years of elementary school (6th to 9th grade) approved in the PNLD 2024, namely: Ways: English for Life and Bridges, each composed of four copies for each year. That was done with the aim of verifying how the collections adapted to the Base Nacional Comum Curricular (BNCC) and the criteria of the PNLD notice, considering the approach to discourse genres and their relationship with the objects of knowledge determined for teaching English. This study is mainly based on the theoretical assumptions of Bakhtin (2002, 2011), who emphasizes that “the richness and variety of discourse genres are infinite, since the virtual variety of human activity is inexhaustible” (2011, p. 280); Marcuschi (2003, p. 19), who defines genres as “socio-discursive entities and forms of social action that are unavoidable in any communicative situation”, which “are characterized as highly malleable, dynamic and plastic textual events”; Bronckart (1999, p. 137), who proposes that “texts are products of language activity in permanent operation in social formations”; in addition to other researchers of textual genres and discourse, such as Rojo and Barbosa (2015) and Bezerra (2017). This research is divided into three stages: contextualization, survey of discourse genres and data analysis. In our analysis, we first verified which discourse genres were common in both collections, and thereafter, we investigated how these genres were approached to comply with the BNCC and the PNLD notice, and, mainly, to prioritize the teaching of the English language. Four discourse genres are recurrent in the collections: comic strip, graphic, culinary recipe, and critical film review. The analysis indicates that both collections present characteristics compatible with what is required by the BNCC and the PNLD notice, justifying their approval in the evaluation. The Ways: English for Life collection approaches discourse genres satisfactorily, for example, in the use of genres as a form of oral and written communication and the emphasis on the constituent elements of the statement (compositional form, theme, and style). However, it lacks some adjustments, such as providing complete information on the conditions for producing a given genre. In addition, the collection could have explored the main genre of the unit in the reading section, stressing the characteristics of the text. Likewise, the Bridges collection shows a satisfactory approach to discourse genres, exploiting the characteristics of the genre and its constituent elements. In short, both collections prioritize the teaching of the English language through different texts that circulate in different social spheres.